Fat in school: applied interdisciplinarity as a basis for consultation in oppressive social context - Clare, Mary M.; Ardron-Hudson, Elise A.; Grindell, Jessica (Journal of Educational and Psychological Consultation, 2015)
Children and youth in schools are subject to the effects of the larger culture's attitudes and values related to body size. When negatively biased, these attitudes and values can have detrimental effects and thus emerge as relevant to educational and psychological consultants. Drawing on the nascent field of Fat Studies with its focus on the cultural meanings attached to large bodies, we identify direct implications of fat phobia for school-age children and youth. Via a brief case example, an initial review of literature, and several examples of health-positive programming, we describe the social justice implications of fat phobia for consultants in school and community settings. In this consideration of the role of consultants for addressing fat bias and supporting health, we also suggest the merit of applied interdisciplinarity as a strong ground for consultation research and practice. The academic area of Fat Studies provides illustration of the integration of disciplinary perspectives (e.g., sociology, anthropology, biology, psychology). Educational and psychological consultation is ideally situated for systematically engaging such interdisciplinarity in support of practical outcomes that are healthy, sustainable, and socially just.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-800-206-439-585 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.mft

Queer youth in family therapy - Harvey, Rebecca G.; Fish, Linda Stone (Family Process, 2015)
Trends in popular belief about same-sex relationships have undergone noteworthy change in the United States over the last decade. Yet this change has been marked by stark polarizations and has occurred at varying rates depending upon regional, community, racial, religious, and individual family context. For queer youth and their families, this cultural transformation has broadened opportunities and created a new set of risks and vulnerabilities. At the same time, youth's increasingly open and playful gender fluidity and sexual identity is complicated by unique intersections of class, race, religion, and immigration. Effective family therapy with queer youth requires practitioner's and treatment models that are sensitive to those who bear the burden of multiple oppressions and the hidden resilience embedded in their layered identities. We present case examples of our model of family therapy which addresses refuge, supports difficult dialogs, and nurtures queerness by looking for hidden resilience in the unique intersections of queer youths' lives. These intersections provide transformational potential for youth, their families and even for family therapists as we are all nurtured and challenged to think more complexly about intersectionality, sexuality, and gender. Las tendencias en la creencia popular acerca de las relaciones entre personas del mismo sexo han sufrido un cambio considerable en Estados Unidos durante la ultima decada. Sin embargo, este cambio se ha producido a ritmos diferentes segun las comunidades locales y regionales, y el contexto familiar individual. En el caso de los jovenes queer y sus familias, esta transformacion cultural ha ampliado oportunidades y creado un nuevo conjunto de riesgos y vulnerabilidades. Los jovenes queer y sus familias, al intentar desarrollarse en numerosos contextos, estan marcados por divergencias crueles en actitudes y creencias. Al mismo tiempo, la fluidez del genero y la identidad sexual cada vez mas abiertas y ludicas de los jovenes estan complicadas por intersecciones unicas de clase, raza, religion e inmigracion. Una terapia familiar eficaz con jovenes queer exige modelos de tratamiento y profesionales que sean sensibles a aquellas personas que cargan sobre sus espaldas numerosas opresiones y una resiliencia oculta incorporada en sus identidades multiples. Presentamos ejemplos de casos de nuestro modelo de terapia familiar que aborda el refugio, respalda los dialogos dificiles y apoya la sexualidad alternativa buscando la resiliencia oculta en las intersecciones unicas de las vidas de los jovenes queer. Estas intersecciones ofrecen posibilidades transformacionales para los jovenes, sus familias e incluso los terapeutas familiares mientras nos estimulan y nos desafian a todos a pensar de forma mas compleja acerca de la interseccionalidad, la sexualidad y el genero.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/008-905-145-849-804 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Adolescent; Family Relations; Family Therapy; Family therapy; Female; Gay; Gender Identity; Homosexuality; Homosexuality; Female; Homosexuality; Male; Humans; Interpersonal Relations; Lesbian; Male; Resilience; Social Identification; Social Isolation; Transgender Persons; Transgendered youth; United States; Vulnerable Populations; Young Adult; adolescent; dept.mft; family relation; family therapy; female; gender identity; homosexuality; human; human relation; lesbianism; male; male homosexuality; procedures; psychology; social behavior; social isolation; statistics and numerical data; transgender; vulnerable population; young adult

Substance abuse prevention: perspectives from india’s addiction treatment professionals - Perumbilly, Sebastian A; Anderson, Stephen A (American Journal of Sociology, 2015)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/045-554-955-113-014 tex.type: [object Object]
Keywords: dept.mft; peer-reviewed